Up a special book series - Disney pixar ([place of publication not identified] [publisher not identified], 2019)
after the passing of his beloved wife Ellie, Carl Fredricksen decides to fulfil their life dream and travel to paradise falls. but when an unexpected vistor hitches a ride and a very talkative dog joins in on the adventure
English stories
Keywords: English stories